An adaptive capacity estimation approach for lithium-ion battery using 10-min relaxation voltage within high state of charge range. (15th January 2023) - Jiang, Bo; Zhu, Yuli; Zhu, Jiangong; Wei, Xuezhe; Dai, Haifeng
Abstract: Capacity estimation is essential for battery health management during the whole lifecycle. The data-driven technique has shown advanced performance in battery capacity estimation. However, the strict limitations on application scenarios and the long duration for feature determination are still the bottlenecks of existing data-driven estimation methods. This study proposes a data-driven capacity estimation method only using 10-min relaxation voltage data, which is adaptable to the high state of charge (SOC) range. The experiments of commercial batteries are designed to investigate the coupling relationship between relaxation voltage, battery aging, and charging cut-off SOC. Further, a novel dual Gaussian process regression (GPR) framework is put forward, in which one GPR is responsible for the battery open-circuit voltage (OCV) estimation using the sequential relaxation voltage feature, and another GPR estimates battery capacity with the corresponding relaxation voltage feature and the estimated OCV. Quantitative experimental results demonstrate that the proposed approach can achieve accurate OCV estimation with extremely sparse voltage data. When SOC is larger than 90%, the capacity estimation achieves a mean absolute error of 2.493% over the battery lifecycle, showing a noticeable improvement over the traditional estimation method. Highlights: A battery capacity estimation approach using 10-min relaxation voltage is proposed. The adaptive capacity estimation method can cover the high SOC range. The sequential voltage features are constructed to realize the multi-state estimation. The proposed approach contains dual Gaussian process regression models.